2010
DOI: 10.1073/pnas.0911359107
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of theArabidopsisCGI-58 homologue produces Chanarin–Dorfman-like lipid droplet accumulation in plants

Abstract: CGI-58 is the defective gene in the human neutral lipid storage disease called Chanarin-Dorfman syndrome. This disorder causes intracellular lipid droplets to accumulate in nonadipose tissues, such as skin and blood cells. Here, disruption of the homologous CGI-58 gene in Arabidopsis thaliana resulted in the accumulation of neutral lipid droplets in mature leaves. Mass spectroscopy of isolated lipid droplets from cgi-58 loss-of-function mutants showed they contain triacylglycerols with common leaf-specific fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
124
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 48 publications
(55 reference statements)
2
124
1
Order By: Relevance
“…Arabidopsis contains many genes that could potentially have this function (Li-Beisson et al, 2013). CGI58 is one candidate, since the protein has lipase activity (Ghosh et al, 2009) and the mutant accumulates TAG in its leaves to around 0.2% of dry weight (James et al, 2010), which is higher than we detected in sdp1. The disruption of fatty acid b-oxidation also leads to TAG accumulation in leaves (Slocombe et al, 2009;James et al, 2010), but the impact on total fatty acid content appears to be small (Yang and Ohlrogge, 2009), unless the tissue is subjected to carbohydrate starvation (Kunz et al, 2009;Slocombe et al, 2009).…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Arabidopsis contains many genes that could potentially have this function (Li-Beisson et al, 2013). CGI58 is one candidate, since the protein has lipase activity (Ghosh et al, 2009) and the mutant accumulates TAG in its leaves to around 0.2% of dry weight (James et al, 2010), which is higher than we detected in sdp1. The disruption of fatty acid b-oxidation also leads to TAG accumulation in leaves (Slocombe et al, 2009;James et al, 2010), but the impact on total fatty acid content appears to be small (Yang and Ohlrogge, 2009), unless the tissue is subjected to carbohydrate starvation (Kunz et al, 2009;Slocombe et al, 2009).…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies have shown that the disruption of several other genes associated with lipid catabolism can also lead to TAG accumulation in vegetative tissues, although heterotrophic tissues have not generally been investigated (Kunz et al, 2009;Slocombe et al, 2009;James et al, 2010). PXA1 is a peroxisomal ATPbinding cassette transporter that is required for fatty acid import for b-oxidation (Zolman et al, 2001), and CGI58 is an enzyme that has been reported to have lipase, phospholipase, and lysophosphatidic acid acyltransferase activities (Ghosh et al, 2009).…”
Section: Tag Accumulation In Sdp1 Roots Is Greater Than In Several Otmentioning
confidence: 99%
See 2 more Smart Citations
“…Arabidopsis CGI-58, a homolog of a mammalian lipase activator (comparative gene identification-58), promotes PXA1 function in leaves but not in germinating seeds (Park et al, 2013), and triacylglycerol accumulates in leaf oil bodies in cgi-58 mutants (James et al, 2010). Moreover, b-oxidation of triacylglycerol from stomatal oil bodies contributes to the ATP production necessary for stomatal opening upon transfer from dark to light (McLachlan et al, 2016).…”
mentioning
confidence: 99%